Abnormal Audit Fee pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2022 dan Faktor yang Mempengaruhinya - Huljannah, Miftha; Djamil, Nasrullah (Basecamp Economics PubMed, 2024)
Abnormal audit fees are very relevant in Indonesia, because the amount of audit fees in Indonesia is still based on deliberations between the auditor and the client. Audit fees that deviate from what they should be either in a higher or lower amount are called abnormal audit fees. In previous research, abnormal audit fees influence economic uncertainty, corporate risk taking and managerial overconfidence. In this research, we will analyze these elements regarding abnormal audit fees in Indonesia by focusing on manufacturing companies listed on the IDX as the research object. By using a purposive sampling technique, 60 manufacturing companies were obtained on the Indonesia Stock Exchange (BEI) for the 2021-2022 period. Panel data regression is used in this research. The results of this research are that economic uncertainty and managerial overconfidence influence abnormal audit fees. Meanwhile, management risk taking does not affect abnormal audit fees.